Transformation of State Religious School Competence: An Analysis of the 1975 Joint Ministerial Decree and Its Implications in Indonesia - Ahmad Salim; Imam Suyuti; Muhammad Gafarurrozi; Laelatul Badriah; Nik Md. Saiful Azizi bin Nik Abdullah (Jurnal Pendidikan Agama Islam, 2024)
Purpose – This study analyses the transformation of state religious school (Madrasah Aliyah Negeri/MAN) competencies in Indonesia following the 1975 Joint Ministerial Decree. It explores the decree’s implications for integrating Islamic values into the national curriculum and its impacts on education quality. Design/methods/approach – A qualitative approach with a multi-site case study design was used. Data were collected through in-depth interviews with stakeholders, including principals, teachers, and alums from three public religious schools in Yogyakarta. Observations and document analyses complemented the interviews, ensuring a comprehensive understanding of the decree’s implementation. Findings – The findings reveal significant variations in implementing the decree across schools. Schools with robust resources and community support effectively integrated the national curriculum with Islamic values, enhancing religious and academic competencies. However, schools with limited resources faced challenges balancing modern academic demands with preserving Islamic identity. Research implications/limitations – The study underscores the importance of tailored policy implementation, considering local contexts and resource availability. A limitation is that it focuses on a specific geographic region, which may not fully capture national variations. Originality/value – This research provides original insights into the interplay between Islamic education and modern educational demands in Indonesia. It contributes to the discourse on integrating traditional religious education within contemporary frameworks to achieve sustainable development goals (SDGs).